2015
DOI: 10.1589/jpts.27.1775
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Swiss ball exercise and resistance exercise on respiratory function and trunk control ability in patients with scoliosis

Abstract: [Purpose] This study compared the effects of Swiss ball exercise and resistance exercise on the respiratory function and trunk control ability of patients with scoliosis. [Subjects] Forty scoliosis patients were randomly divided into the Swiss ball exercise group (n= 20) and resistance exercise group (n = 20). [Methods] The Swiss ball and resistance exercise groups performed chest expansion and breathing exercises with a Swiss ball and a therapist’s resistance, respectively. Both groups received training 30 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Schroth exercises applied for five sessions in the two weeks with a daily home program in supervised sessions improved the quality-of-life and back muscle endurance 35 ) . Swiss ball exercise and chest resistance exercise training applied for 30 min per day, five times per week, for eight weeks were effective in improving the static balancing ability 36 ) , the respiratory function and trunk control ability of patients with scoliosis 37 ) . Adding Game-Trak to three dimensional (3D) interactive game to specific physiotherapeutic scoliosis-specific exercises intervention improved exercise performance 38 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Schroth exercises applied for five sessions in the two weeks with a daily home program in supervised sessions improved the quality-of-life and back muscle endurance 35 ) . Swiss ball exercise and chest resistance exercise training applied for 30 min per day, five times per week, for eight weeks were effective in improving the static balancing ability 36 ) , the respiratory function and trunk control ability of patients with scoliosis 37 ) . Adding Game-Trak to three dimensional (3D) interactive game to specific physiotherapeutic scoliosis-specific exercises intervention improved exercise performance 38 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that correction and respiratory treatment are essential because of the bending of the thoracic cage, which weakens the respiratory muscle and lowers cardiopulmonary function 11 ) . Various core and breathing exercises are used to treat scoliosis 12 , 13 ) . The treatment effects of the Schroth therapy, a recent therapeutic exercise, have been reported 14 , 15 ) .…”
Section: Introductionmentioning
confidence: 99%
“…While there is an agreement that individuals who underwent spinal fusion for AIS can perform maximal-effort sport movements without inducing an acute injury [15][16][17][18][19][20][21], some controversy still exists surrounding when the patients should return to sports after surgery [21]. Surgeons and clinicians are often cautious, to avoid a patient from undergoing spinal trauma during movements such as rotations and bending [22].…”
Section: Discussionmentioning
confidence: 99%